Orbital cellulitis due to sinusitis in children: diagnosis and multidisciplinary approach (Research, Society and Development, 2020)
Background: Although rare, sinusitis is one of the main factors for orbital complications, such as orbital cellulitis and is highly prevalent in children. Its treatment must be done early, as the condition can evolve and present secondary complications such as meningitis, thrombosis of the cavernous sinus and even lead to death. In addition, the same should be done by a multidisciplinary team so that the treatment is effective and the prognosis is improved. Objective and case report: The objective is report a 4-year-old patient diagnosed with orbital cellulitis due to sinus complications that affected the facial sinuses and spread to the right eye, causing fever, malaise and amaurosis. The treatment was performed by Otorhinolaryngology by endoscopic surgery and after that the patient evolved well. Conclusion: In view of this, the improvement in the prognosis can be highlighted if both sinusopathy and the complication that, in this case, was orbital cellulitis are properly diagnosed and treated.